Technology-based learning: developing educational videos for immunology practical courses - Amilia Shaqina Rizuan Ong (2016)
To develop educational videos for immunology practical course for technology-based learning. This research study was conducted in 2016 in School of Biological Sciences (SBS), NTU. Students of BS3331 Undergraduate Advanced Experimental Biology (UAEB)-Applied Immunology and general public tertiary students were given separate survey questions. Tertiary students from the general public were further distributed into those who had laboratory practical as part of their course of study. Data were then collated from the respondents from both sets of surveys. From this research study, we found that 90% of the students have used video demonstrations to aid in their learning before. We also found that more than 89% of the general tertiary students and 92% of BS3331 students found the videos to be helpful in carrying out their laboratory practical procedures. The main focus of this FYP was to develop the educational videos that can enhance students’ learning process in laboratory settings and assists students’ preparation and execution of experimental procedures. This research study also examined the preferred methods of learning by tertiary students and addressed issues that students faced during the laboratory practical course. We also assess the factors that can be use to develop specific content of the educational videos for all students. Even though data pertaining to effectiveness of the videos data collected was not exhaustive, research have shown that the use of educational videos for all learning environments will be widespread in the near future.